Venture Capital-backed Firms, Unavoidable Value-destroying Trade Sales, and Fair Value Protections - Casimiro Antonio Nigro; Jor̈g R. Stahl (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
This paper investigates the implications of the fair value protections contemplated by the standard corporate contract (i.e., the standard contract form for which corporate law provides) for the entrepreneur-venture capitalist relationship, focusing, in particular, on unavoidable value-destroying trade sales. First, it demonstrates that the typical entrepreneur-venture capitalist contract does institutionalize the venture capitalist's liquidity needs, allowing, under some circumstances, for counterintuitive instances of contractually-compliant value destruction. Unavoidable value-destroying trade sales are the most tangible example. Next, it argues that fair value protections can prevent the entrepreneur and venture capitalist from allocating the value that these transactions generate as they would want. Then, it shows that the reality of venture capital-backed firms calls for a process of adaptation of the standard corporate contract that has one major step in the deactivation or re-shaping of fair value protections. Finally, it argues that a standard corporate contract aiming to promote social welfare through venture capital should feature flexible fair value protections
urn:nbn:de:hebis:30:3-616417
Keywords: K22; M13; 330; Private equity; Venture capital; Start-ups; Entrepreneurship; Innovation; Corporate governance; Private ordering; Drag-along rights; Trade sales; Corporate law; Fair value; Appraisal rights; Law and economics; Law and finance